ALIENATION AND ECOACTIVISM IN SELECTED WORKS ON THE NIGER DELTA CRISIS (2014)
The discourse of alienation, provoked by environmental despoliation due to the activities of multinational oil companies in the Niger Delta region, is aptly captured in literary works. Previous studies on literary texts about the Niger Delta crisis have identified the negative socio-economic and political impacts of oil exploitation as responsible for the ecoactivism in the Niger Delta, neglecting the role of alienation or erosion of self in the fueling of the crisis. This study, therefore, examines the indicators of erosion of self as projected in selected prose texts on the Niger Delta crisis. This is with a view to establishing how the literary writers connect ecoactivism to the erosion of self. Karl Marx's and Marilyn Nissim-Sabat's postulations on alienation as well as Lawrence Buell's theory on practical commitment to the environment were adopted based on their concern with alienation and ecoactivism, and as implicated in the Niger Delta crisis. Six prose works: Saro-Wiwa's A Month and a Day (AMAD), a memoir; Okpewho's Tide (T); Ojaide's The Activist (TA); Egbuson's Love My Planet (LMP); Agary's Yellow-Yellow (YY) and Habila's Oil on Water (OOW) were chosen. Their selection was based on the shared experiential knowledge of all but one of the writers, and the themes of alienation and ecoactivism, which are common to them. These texts were subjected to literary analysis. Three indicators of alienation or erosion of self-consciousness and two indicators of ecoactivism are differently portrayed in the six texts. Alienation is unveiled through the following: pictures of degraded ecosystem; internal division; presentation of the people as victims as well as protagonists. Ecoactivism is illustrated through ecoterrorism; and non-violent eco-campaign. All the six texts, employing pathos, capture the feeling of alienation of the people of Niger Delta through appalling pictures of the degraded environment as a result of the activities of multinational oil companies. Saro-Wiwa's (AMAD), Okpewho's T, Ojaide's TA, Egbuson's LMP and Habila's OOW illustrate the people's erosion of self as a result of divisions among them, due to financial inducements from the Nigerian state and the multinational oil companies. Okpewho's T, Saro-Wiwa's AMAD, Ojaide's TA and Egbuson's LMP, through antithetical pictures, capture the people's loss of self by presenting them as victims of internal/external exploitation as well as protagonists against internal/external foes. Three of the texts, namely: Ojaide's TA, Egbuson's LMP and Habila's OOW present violence/ecoterrorism against the perceived internal/ external foes of the people as a means of preserving the environment. Saro-Wiwa's AMAD, Okpewho's T and Agary's YY reveal urgent non-violent eco-campaign in the area. Ecological degradation and internal divisions are linked by the six texts to the oil and gas exploration activities of the multinational oil companies and these generate a sense of alienation that leads to intense ecoactivism in the area. Three indicators of erosion of self, which connect with ecoterrorism and non-violent eco-campaign, are manifest in the selected texts through the use of pathos and antithesis. These reveal the writers' construction of self as a contingence on ecoactivism in the Niger Delta crisis.